Peningkatan Kinerja Karyawan Dengan Pelatihan Service Excellence Pada Waroeng Gaul - Puja Lailatul Rahmi; Zakia Putri Aulia; Selvi Novia Dewita Sari; Andry Novrianto (CV. ITTC INDONESIA, 2025)
This study aims to analyze the impact of service excellence training on employee performance at Waroeng Gaul Sawahan, Padang City. Using a qualitative approach with a case study method, the study was conducted through in-depth interviews and direct observation of 40 employees. The results showed that service excellence training had a positive impact on improving employee communication skills, friendliness, and professionalism in serving customers. Significant changes were seen in response speed, service proactivity, and reduction in errors in presentation. However, challenges were still encountered, especially related to variations in employee mood and consistency of service under pressure. Management has implemented a reward system and regular evaluation to maintain work motivation. This study concludes that service excellence training is effective in improving employee performance and creating a more satisfying customer experience at Waroeng Gaul Sawahan.